2006
DOI: 10.1345/aph.1g723
|View full text |Cite
|
Sign up to set email alerts
|

Human Papillomavirus Vaccines

Abstract: Cervarix and Gardasil are effective for prevention of HPV infection and cervical lesions. Issues remaining to be addressed include duration of protection, efficacy for prevention of cervical cancer, optimal age for vaccination, feasibility of application to the developing world, the ideal combination of HPV subtypes, and the most efficient combination of vaccination and cervical cancer screening.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0
2

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(32 citation statements)
references
References 40 publications
(44 reference statements)
0
30
0
2
Order By: Relevance
“…Cervarix is an HPV16/ 18 L1 virus-like particle vaccine that offers complete protection against HPV16-and 18-associated precancerous lesions as well as substantial protection against types 45 and 31 (Harper et al 2006). Gardasil is a quadrivalent vaccine made of the major capsid protein (L1) of high-risk HPV types 16 and 18, and low-risk types 6 and 11, which has been found to prevent 100% CIN2/3 and adenocarcinoma in situ associated with HPV16 and 18 infections (Schmiedeskamp and Kockler 2006). These vaccines may prove to be effective against a majority of cervical cancers, but may not benefi t women infected with rarer HPV types.…”
Section: Discussionmentioning
confidence: 99%
“…Cervarix is an HPV16/ 18 L1 virus-like particle vaccine that offers complete protection against HPV16-and 18-associated precancerous lesions as well as substantial protection against types 45 and 31 (Harper et al 2006). Gardasil is a quadrivalent vaccine made of the major capsid protein (L1) of high-risk HPV types 16 and 18, and low-risk types 6 and 11, which has been found to prevent 100% CIN2/3 and adenocarcinoma in situ associated with HPV16 and 18 infections (Schmiedeskamp and Kockler 2006). These vaccines may prove to be effective against a majority of cervical cancers, but may not benefi t women infected with rarer HPV types.…”
Section: Discussionmentioning
confidence: 99%
“…1 Well-documented evidence exists showing that cervical cancer is related to persistent Human Papillomavirus (HPV) infection. [2][3][4][5] Using sensitive Polymerase Chain Reaction (PCR) techniques, HPV-DNA is detected in almost 100% of invasive cervical cancers. 4,[6][7][8][9][10][11][12] The highest prevalence of HPV-induced cervical preneoplastic changes occurs in the third decade, 13 while the mean age of invasive carcinoma occurs in the middle of the sixth decade, 14 suggesting a prolonged latent phase of genital infection before the onset of malignant disease.…”
Section: Introductionmentioning
confidence: 99%
“…[6] Cervarix, a bivalent vaccine, targets HPV 16 and HPV 18, which are responsible for 70% of cervical cancers. [28] All studies showed HPV-type speciÞ c protection; Cross-protection was noted in one study. [26] ; The age of women in these studies ranged from 15 to 26 years Gardasil, a quadrivalent vaccine, also targets HPV 16 and HPV 18, plus the HPV types 6 and 11 responsible for more than 80% of genital warts.…”
Section: Emerging Hpv Vaccines Emerging Hpv Vaccinesmentioning
confidence: 96%